دور البنوك الخضراء في مواجهة التغير المناخي في باكستان - عليش، فطيمة (جامعة الوادي University of Eloued, 2025)
هدفت هذه الدراسة إلى تسليط الضوء على دور البنوك الخضراء في باكستان كخطوة حيوية نحو تحقيق الاستدامة البيئية والاقتصادية في القطاع المصرفي. من خلال التعديلات التي أجراها البنك المركزي على اللوائح المصرفية وتشجيع التمويل الأخضر، تسعى البنوك إلى تقليل التأثيرات البيئية والمساهمة في مواجهة التغير المناخي. أصبح التمويل الأخضر مفهومًا جديدًا في القطاع المصرفي رغم التحديات القانونية، حيث تبنت البنوك تدريجيًا ممارسات خضراء استجابة للمسؤولية الاجتماعية والفوائد الاقتصادية ومخاطر الاستدامة. كما ركزت على تقليل المخاطر البيئية ودعم الأعمال التجارية الخضراء. ورغم التقدم، لا تزال البنوك بحاجة إلى مزيد من الدعم لتحقيق الاستدامة المالية والبيئية، بما يتماشى مع أهداف التنمية المستدامة للأمم المتحدة. This study aimed to highlight the role of green banks in Pakistan as a major step towards achieving better sustainability in the Gaza Strip. Through the contributions made by the central bank on regulations and encouraging green finance, banks are there to impact environmental impacts and contribute to combating climate change. Finance has become a new concept in the sector despite the legal provisions; banks have adopted green practices in addition to social responsibility, economic benefits, and sustainability risks. It has also focused on a large number of vehicles with green numbers. Despite the progress, banks do not seek support for achieving financial and environmental sustainability, including achieving the sustainable development goals in the United States.
The Role of Green Banks in Addressing Climate Change in Pakistan
مقال
Keywords: البنوك الخضراء; التمويل الأخضر; التغير المناخي; البنك الأخضر الباكستاني; Green banking; green finance; climate change